2013
DOI: 10.3389/fnhum.2013.00908
|View full text |Cite
|
Sign up to set email alerts
|

Drift and ownership toward a distant virtual body

Abstract: In body ownership illusions participants feel that a mannequin or virtual body (VB) is their own. Earlier results suggest that body ownership over a body seen from behind in extra personal space is possible when the surrogate body is visually stroked and tapped on its back, while spatially and temporal synchronous tactile stimulation is applied to the participant's back. This result has been disputed with the claim that the results can be explained by self-recognition rather than somatic body ownership. We car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 25 publications
(50 reference statements)
3
31
0
Order By: Relevance
“…A similar result found that "visual capture by a fake hand (without any synchronous or asynchronous tactile stimulation) affects body ownership in a group of hemiplegic patients with or without disturbed sensation of limb ownership" (Martinaud et al, 2017, p. 174). On the other hand, others do not observe significant differences between first and third person perspectives for embodiment (Pomés and Slater, 2013).…”
Section: Affective Motor and Spatial Embodimentmentioning
confidence: 93%
“…A similar result found that "visual capture by a fake hand (without any synchronous or asynchronous tactile stimulation) affects body ownership in a group of hemiplegic patients with or without disturbed sensation of limb ownership" (Martinaud et al, 2017, p. 174). On the other hand, others do not observe significant differences between first and third person perspectives for embodiment (Pomés and Slater, 2013).…”
Section: Affective Motor and Spatial Embodimentmentioning
confidence: 93%
“…There has been a lot of work on building virtual embodiment technology (Spanlang et al, 2013(Spanlang et al, , 2014, studying the conditions that can lead to such body ownership illusions (Slater et al, , 2010bSanchez-Vives et al, 2010;Borland et al, 2013;González-Franco et al, 2013;Llobera et al, 2013;Slater, 2013, 2014;Pomes and Slater, 2013;Blom et al, 2014;Kokkinara and Slater, 2014) and exploring the effects of distortions away from the normal form of a person's actual body (Slater et al, 2010b;Normand et al, 2011;Kilteni et al, 2012;Steptoe et al, 2013). There have also been studies on how illusions of body ownership might result in various changes to the real body.…”
Section: The Virtual Bodymentioning
confidence: 99%
“…However, researchers have demonstrated that immersive VR systems can be used to create body ownership illusions, in which "healthy subjects experience an artificial body as if it were their own physical body" (Maselli and Slater, 2013). In other words, users may unconsciously accept an avatar representation of themselves as their own body and respond to events involving their avatar, such as possible harm (González-Franco et al, 2014), uncontrolled movements (Pomes and Slater, 2013), expected social behaviors (Kilteni et al, 2013), and even time travel (Friedman et al, 2014). If immersive technologies can be used to induce such body ownership illusions, particularly time travel, they can clearly be used to place the audience within a news story.…”
Section: Body Ownershipmentioning
confidence: 99%